Hotelling meets Shaked and Sutton: A unified linear model of product differentiation - Armin Schmutzler (University of Zurich, Department of Economics, 2025)
This paper provides a simple unified discrete-choice framework for analyzing differentiated duopolies. This framework nests models of horizontal and vertical differentiation, including standard textbook models (Hotelling and Shaked-Sutton). Contrary to these models, it also applies to economic environments where horizontal differentiation coincides with positive correlation of product valuations across consumers, and environments where vertical differentiation coincides with negative correlation. The paper provides an equilibrium characterization that is applicable independently of the type of differentiation and the sign of the valuation correlation.
Keywords: D43; L13; 330; Duopoly; Differentiated Products; Price Competition